2018
DOI: 10.1186/s40813-018-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cystoisospora suis in faeces of suckling piglets – when and how? A comparison of methods

Abstract: BackgroundCystoisospora suis is the causative agent of porcine neonatal coccidiosis, a diarrheal disease which affects suckling piglets in the first weeks of life. Detection of oocysts in the faeces of infected animals is frequently hampered by the short individual excretion period and the high fat content of faecal samples. We analysed oocyst excretion patterns of infected piglets, evaluated different detection methods for their detection limit and reproducibility, and propose a sampling scheme to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 38 publications
0
38
1
Order By: Relevance
“…These rates are in line with a study from Sweden that showed a cumulative herd prevalence of 76% in piglets up to 4 weeks (3). However, a direct comparison of infection rates between studies must be interpreted with caution due to non-representative sampling and different diagnostic methods with different sensitivities (20,21). As Meyer et al (22) pointed out, individual samples from piglets from a litter pooled to a litter sample are preferable for examination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These rates are in line with a study from Sweden that showed a cumulative herd prevalence of 76% in piglets up to 4 weeks (3). However, a direct comparison of infection rates between studies must be interpreted with caution due to non-representative sampling and different diagnostic methods with different sensitivities (20,21). As Meyer et al (22) pointed out, individual samples from piglets from a litter pooled to a litter sample are preferable for examination.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to sample at least 10% of the litters that were born during the examination period, but a maximum of 30 litters/farms. To increase sensitivity each litter was sampled twice in one-week intervals due to the short periods of oocyst excretions (20). Number of litters examined/farm are shown in Supplementary Table 1.…”
Section: Farms and Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The GAM proteins EmGam56 and EmGam82 were identified as antigens that conferred protection against different species of chicken Eimeria due to their conserved nature. A subunit vaccine for immunization was previously developed from E. maxima gamont proteins and commercialized for the prevention of coccidiosis [9,52].…”
Section: Genes Linked To Sexual Stagesmentioning
confidence: 99%